Lung cancer, proximity to industry, and poverty in northeast England. - Pless-Mulloli, T (1998)
This study assesses whether deprived populations living close to industry experience greater mortality from lung cancer than populations with comparable socioeconomic characteristics living farther away. Mortality data, census data, a postal survey of living circumstances, historic and contemporary data on air quality and a historic land-use survey were used. Analysis was based on two conurbations in England, Teesside and Sunderland. Housing estates in Teesside were selected based on socioeconomic criteria and distinguished by proximity to steel and chemical industries; they were grouped into three zones: near (A), intermediate (B), and farther (C), with a single zone in Sunderland. We included 14,962 deaths in 27 estates. Standardized mortality ratios (SMR) for lung cancer [International Classification of Diseases #9 (ICD-9) 162] and cancers other than lung (ICD-9 140-239, excluding 162), and sex ratios were calculated. Mortality from lung cancer was well above national levels in all zones. For men, a weak gradient corresponding with proximity to industry at younger ages reversed at older ages. In women 0-64 years of age, stronger gradients in lung cancer mortality corresponded with proximity to industry across zones A, B, and C (SMR = 393, 251, 242, respectively). Overall rates in Teesside were higher than Sunderland rates for women aged 0-64 years (SMR = 287 vs. 185) and 65-74 years (SMR = 190 vs. 157). The association between raised lung cancer mortality and proximity to industry in women under 75 years of age could not be explained by smoking, occupation, socioeconomic factors, or artifact. Explanations for differences between men and women may include gender-specific occupational experiences and smoking patterns. Our judgment is that the observed gradient in women points to a role for industrial air pollution.